PELATIHAN MICROSOFT OFFICE EXCEL SEBAGAI UPAYA PENINGKATAN KEMAMPUAN MAHASISWA DALAM MENGOLAH DATA - Radhya Yusri; Sofia Edriati; Rival Yuhendri (STKIP PGRI Sumatera Barat, 2020)
The difficulty of students in operating Microsoft Excel programs as one of the data processing programs as a major factor in the low ability of students to process data. The training activities aim to make participants comprehensively understand the material presented, so that it can be implemented applicatively in the world of work and have the professional ability to operate Microsoft Excel and deliver participants to the International Microsoft Office Specialist Excel Certification. The method used in the implementation of this activity is teaching in a computer laboratory, tutorials (mentoring) using Microsoft Excel 2010 modules, discussions and questions and answers. The activity was carried out at the STKIP PGRI West Sumatra Laboratory. The population is the 2017 STKIP PGRI West Sumatra Mathematics Education Study Program students who will graduate. Based on the activities carried out, it was obtained that out of 44 participants who were registered to take part in the training and international certification exam, only 29 participants took part in the training. Of the 29 participants who could take the international certification exam only 22 participants. There were 45% of participants who passed the certification exam so that they received the MOS Certified certificate from Microsoft. While 32% of participants received a Certificate of Completion certificate and as many as 23% of participants received a Certificate of Attendance certificate. So it can be concluded that the training provided is able to improve the ability of students to operate Microsoft Excel.